Determination of Drag and Lift using ANSYS CFD Flotran Simulation - Sulaiman, S. A.; Horng, C. J. (2005)
Aerodynamic drag and lift in a moving object are important properties for efficient designs in various engineering applications; hence researches are continually undertaken to better understand them. The drag and lift forces can be determined through experiments using wind tunnel testing, in which the design model has to be placed in the test section. Nevertheless due to several factors including its complexity, the cost, and the space it takes, not many researchers are capable to perform wind tunnel testing. On the other hand, with the availability of Computational Fluid Dynamics (CFD) modeling, pressure distribution on the external surface of the model can be obtained and exploited to determine lift and drag. This paper presents a computational method to deduce the lift and drag properties, which can reduce the dependency on wind tunnel testing. The study was done on air flow over a two-dimensional cylindrical object using ANSYS CFD Flotran to obtain the surface pressure distribution, from which drag and lift were calculated using integral equations of pressure over finite surface areas. In addition the drag and lift coefficients were also determined. The simulation was repeated for various Reynolds numbers to check the robustness of the method. The CFD simulation results show close agreement with those of the experiments, thus suggesting a reliable alternative to experimental method in determining drag and lift.